Total Flavonoid dan Aktivitas Antioksidan Food Bar Torbangun – Katuk terhadap Efektivitas Produksi ASI : Total Flavonoid and Antioxidant Activity of Food Bar Torbangun – Katuk on The Effectiveness of Breast Milk Production - Laeli Lutfiani; Nanang Nasrulloh (Amerta Nutrition, 2023)
Background: The main reason for discontinuing exclusive breastfeeding is the low milk supply. Torbangun and Katuk are galactagogues that can stimulate milk production and be modified into food bars to increase breast milk production. Modifying the food bar using Torbangun and Katuk is food fortification to increase milk production for breastfeeding mothers. Objectives: This study aimed to identify the total flavonoids and antioxidant activity of Torbangun flour, Katuk flour, and food bar Torbangun Katuk products and to analyze the effectiveness of Torbangun Katuk food bar in breastfeeding mothers Methods: This was pre-experimental with a pre-test and post-test design to analyze milk production before and after consuming food bars. Raw materials and food bar products were analyzed for total flavonoids with aluminum chloride (AlCl3) and antioxidant activity using the DPPH (1,1-diphenyl-2-picrylhydrazil) method. The food bar had 2.5% Torbangun flour and 5% Katuk flour. The effectiveness test was conducted on ten breastfeeding mothers. Effectiveness was seen from changes in breast milk volume before and after consuming food bars with pairing T test for analysis. Results: chemical analysis showed that the total flavonoids of Torbangun and Katuk flour were 4.06 mg/g and 5.30 mg/g, and antioxidants in Torbangun and Katuk flour were 39.77 ppm and 307.96 ppm, respectively. Furthermore, the total flavonoids and antioxidant activity of the Torbangun Katuk food bar product were 0.36±0.06 mg/g and 116.01±36.83 ppm, respectively. The effectiveness results showed an increase of 54.98% between the average breast milk volume before and after consuming food bars. Giving food bars significantly affected breastmilk production (p<0.05).  Conclusions: Torbangun flour and Katuk flour have the potential as food additives to increase breast milk production.